The Different Classification of Hospitals Impact on Medical Outcomes of Patients in China - Li, Lele; Du, Tiantian; Zeng, Siyu (Frontiers in Public Health, 2022)
Background: In China, different classifications of hospital (COH) provide treatment for patients with different degrees of illness, COH plays an important role in Chinese medical outcomes, but there is a lack of quantitative description of how much impact the results have. The objective of this study is to examine the correlation between COH on medical outcomes with the hope of providing insights into appropriate care and resource allocation. Methods: From the perspective of the COH framework, using the Urban Employee Basic Medical Insurance (UEBMI) data of Chengdu City from 2011 to 2015, with a sample size of 512,658 hospitalized patients, this study used the Nested Multinomial Logit Model (NMNL) to estimate the impact of COH on the medical outcomes. Results: The patients were mainly elder, with an average age of 66.28 years old. The average length of stay was 9.61 days. The female and male gender were split evenly. A high level of hospitals is positively and significantly associated with the death and transfer rates (p<0.001), which may be related to more severe illness among patients in high COH hospitals. Conclusions: COH made a difference in the medical outcomes significantly. COH should be reasonably selected according to disease types to achieve the optimal medical outcome. So, China should promote the construction of a tiered delivery system.